2016
DOI: 10.1080/14767058.2016.1253056
|View full text |Cite
|
Sign up to set email alerts
|

The effect of music therapy on the cardiac activity parameters of a fetus in a cardiotocographic examination

Abstract: Music therapy is a noninvasive and uncostly method, significantly improving wellbeing-indicative fetal parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…Recent studies have shown that music can help pregnant women to relax 96–99. Listening to music can also lead to fetal effects such as an increase in fetal movements and a decrease in uterine contractions 100 101. An increase in fetal movement may be associated with fetal well-being 41.…”
Section: Moving Forward: Prenatal Relaxation Techniques and Their Effmentioning
confidence: 99%
“…Recent studies have shown that music can help pregnant women to relax 96–99. Listening to music can also lead to fetal effects such as an increase in fetal movements and a decrease in uterine contractions 100 101. An increase in fetal movement may be associated with fetal well-being 41.…”
Section: Moving Forward: Prenatal Relaxation Techniques and Their Effmentioning
confidence: 99%
“…At 16 weeks the unborn baby is particularly receptive to its mother's voice. It is fascinating that around 24 weeks, the babies develop preferences for music while in the womb [31] Recent research has shown that music can help pregnant women relax.. Music can also cause foetal effects such as increased foetal movements and decreased uterine contractions. [32][33] An increase in fetal movement may be associated with fetal well-being.…”
Section: Garbhasangeeta (Music For the Fetus)mentioning
confidence: 99%
“…The researchers concluded that usage of music may shorten the time necessary for an NST (non-stress test) [21].…”
Section: An Overview Of Studiesmentioning
confidence: 99%